Plant pangenome: impacts on phenotypes and evolution - Tranchant-Dubreuil, C.; Rouard, M.; Sabot, François (Wiley, 2019)
With the emergence of low‐cost high‐throughput sequencing technologies, numerous studies have shown that a single genome is not enough to identify all the genes present in a species. Recently, the pangenome concept has become widely used to investigate genome composition of a collection of individuals. The pangenome consists in the core genome, which encompasses all the sequences shared by all the individuals, and the dispensable genome, composed of sequences present in only some individuals. Pangenomic analyses open new ways to investigate and compare multiple genomes of closely related individuals at once, and more broadly new opportunities for optimising breeding and studying evolution. This emerging concept combined with the power of the third‐generation sequencing technologies gives unprecedented opportunities to uncover new genes, to fully explore genetic diversity and to advance knowledge about the evolutionary forces that shape genome organisation and dynamics.